L’animazione dell’embrione in Alberto Magno e Tommaso d’Aquino (I-II) - Labeaga, José A. Izquierdo (Alpha omega, 2019)
The article develops the different opinions of Albert the Great and of Thomas Aquinas on the theme of the spiritual animation of the embryo (agents, causality, process, moment), to which they apply their encyclopaedic medical erudition and their philosophical knowledge of an Aristotelian approach. The article presents the difficulties which they found in the face of the very incomplete medical science of their time, which rendered more reasonable the thesis of a delayed animation of the embryo, up to the 40th day. Albert explains the dynamic of animation as similar to the art involved in the practical intellect. Thomas, on the other hand, seeks to save a certain autonomous substantiality of the embryo once it is more defined, in which the embryo proceeds under the totipotent energy of the semen, and he articulates its development through a graduated series of successive generations. The appendix offers the translation of two texts of Albert and of one of Thomas.